(untitled) (Czech Journal of International Relations, 2015)
Edward Luttwak: The rise of China vs. the logic of strategy. 1. vydání. Cambridge, Massachusetts: Harvard University Press, 2012, 320 stran, ISBN 978-0-674-06642-7.